Study on stresses of head cover bolts in a pump turbine based on FSI. Issue 4 (July 2021) - Luo, Yongyao; Chen, Funan; Chen, Liu; Wang, Zhengwei; Yu, Jixing; Zhu, Xingbing; Zhao, Zhiwen; Ren, Shaocheng; Li, Jinwei; Lu, Xiaokang
Abstract: The stresses of head cover bolts in a pump turbine were analyzed based on Fluid-Structure-Interaction (FSI). A nonlinear finite element model including head cover, bolts and stay ring was set up by means of contact elements, two head cover models with different flanges were set up to evaluate the effect of head cover to bolts. Results showed that both the uneven pressure distribution and the uneven head cover structure along the circumference have great influence on the stresses of the bolts. In this study, for the head cover with double flange, the single bolt has larger axial stresses amplitude along the outside circle, and the average values of the axial stresses for the 96 bolts are larger too, as a result, the bolts have higher average relative stiffness.